R REALIZATION OF THE PATIWANGI CEREMONY IN NYEROD WEDDING IN TEMESI VILLAGE GIANYAR DISTRICT, GIANYAR DISTRICT: REALIZATION OF THE PATIWANGI CEREMONY IN NYEROD WEDDING IN TEMESI VILLAGE GIANYAR DISTRICT, GIANYAR DISTRICT - I Ketut Surija, Ni Ketut Oktapiani; Kiriana, I Nyoman; Putra, Kadek Dwi Sentana (UHN IGB Sugriwa Denpasar, 2025)
Traditional ceremonies in Bali play an important role in the life cycle of society, including in maintaining social and spiritual harmony. One of the ceremonies that attracts attention is the Patiwangi ceremony, which is carried out in the context of Nyerod marriage. This ceremony aims to purify individuals who change dynasties through marriage, so that it becomes a symbol of harmony and integration in society. This study focuses on the implementation of the Patiwangi ceremony in Temesi Traditional Village, Gianyar District, Gianyar Regency, which has its own uniqueness in its local traditions. Nyerod marriage, as a form of marriage between individuals from different dynasties, often poses challenges in the traditional order of Balinese society. The Patiwangi ceremony is a means to overcome this dynamic by harmonizing the social and spiritual relationships of individuals with their environment. The implementation of the ceremony involves various traditional elements, including traditional leaders and the bride and groom's families. This tradition also strengthens social solidarity in the community, as stated by anthropological theories related to ritual and culture. However, globalization and modernization bring challenges to the sustainability of this tradition. The younger generation is starting to lose their deep understanding of the philosophical value of the Patiwangi ceremony. Modernization often contributes to the erosion of traditional values if it is not balanced with efforts to preserve culture. Therefore, this study also examines the extent to which the Patiwangi tradition can remain relevant amidst social and cultural changes in Temesi Traditional Village. This study aims to understand the reasons why people carry out the Patiwangi ceremony, the implementation process, and the community's perception of this tradition. The results of the study indicate that the Patiwangi ceremony has significant spiritual, social, and cultural values, despite being faced with various challenges, such as high costs and the influence of external cultures. These findings provide an important picture of the sustainability of tradition in the modern era. This study provides academic and practical contributions to the study of Balinese traditional traditions, especially in the context of Nyerod marriage and the Patiwangi ceremony. The results of the study are expected to provide recommendations for the community and stakeholders in preserving the noble values contained in this ceremony so that they are maintained for future generations. Keywords: Patiwangi Ceremony, Nyerod Marriage